A rare case of congenital absence of ribs in a newborn baby (Indian Journal of Case Reports, 2024)
Congenital absence of ribs is a rare condition. The defect is generally unilateral, and the first rib is usually unaffected. We report a case of congenital absence of ribs in an early-term (37 + 1 week), female baby. The 5th and 6th ribs on the right side were absent. The baby had mild respiratory distress which resolved within 1 day and had no other congenital anomolies. Rarely, it can result in severe lung restriction and cor pulmonale.